Quantitative analysis of the effect of microtubule-targeting drugs on the microtubule cytoskeleton of breast cancer cells with different invasive properties - Michallet, Sophie; Bosc, Lauriane; Lafanechère, Laurence (Comptes Rendus. Chimie)
The characterization of microtubule-targeting drugs at the cellular level is an essential step in the development of drugs targeting the microtubule network. To that aim, we have previously developed a quantitative cell-based assay easy to perform in microplates that requires only a luminescence reader and no microscopic analysis. Here, we show that this assay can be easily adapted to different breast cancer cell lines. An ideal application of this test could be the comparative analysis of the response of human tumor samples to different microtubule targeting drugs, to optimize therapeutic treatment.